1996
DOI: 10.1083/jcb.134.6.1563
|View full text |Cite
|
Sign up to set email alerts
|

Is plasminogen activator inhibitor-1 the molecular switch that governs urokinase receptor-mediated cell adhesion and release?

Abstract: Abstract. Induction of the urokinase type plasminogen activator receptor (uPAR) promotes cell adhesion through its interaction with vitronectin (VN) in the extracellular matrix, and facilitates cell migration and invasion by localizing uPA to the cell surface. We provide evidence that this balance between cell adhesion and cell detachment is governed by PA inhibitor-1 (PAl-l). First, we demonstrate that uPAR and PAL1 bind to the same site in VN (i.e., the amino-terminal somatomedin B domain; SMB), and that PAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
382
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(403 citation statements)
references
References 54 publications
19
382
2
Order By: Relevance
“…However, recent works have demonstrated that uPA, uPA-R and PAI-I influence cell adhesion in a process independent of uPA-mediated proteolysis (Waltz and Chapman, 1994;Deng et al, 1996). The possibility of such influence on cell adhesion in our model remains unknown and further studies should be performed to understand the mechanism by which TGF-PI and other inhibitory agents regulate cell adhesion/migration in the context of the uPA system.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, recent works have demonstrated that uPA, uPA-R and PAI-I influence cell adhesion in a process independent of uPA-mediated proteolysis (Waltz and Chapman, 1994;Deng et al, 1996). The possibility of such influence on cell adhesion in our model remains unknown and further studies should be performed to understand the mechanism by which TGF-PI and other inhibitory agents regulate cell adhesion/migration in the context of the uPA system.…”
Section: Discussionmentioning
confidence: 89%
“…The simultaneous upregulation of uPA and PAI-I in the tumour cells should be considered as being complementary: increased cell-associated uPA induces pericellular protein degradation, favouring cell detachment, while increased PAI-1 levels reduce indiscriminant extracellular matrix degradation, which would deprive invasive cells of the anchorage necessary for cell locomotion. Moreover, Deng et al (1996) have recently reported that PAI-I promotes cell detachment by interacting with vitronectin, independent of its activity to function as a protease inhibitor. In our study, although TGF-,B1 strongly increased uPA and PAI-I in MDA-MB-231 cells, it did not inhibit cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the release of cells from this matrix protein by an excess of PAI-1. Therefore, the delicate balance between cell adhesion and cell detachment has been proposed to be governed by PAI-1 [53].…”
Section: Physiological Inhibitors Of the Plasminogen Systemmentioning
confidence: 99%
“…There was a significant difference between the cells with and without PAI-1-stab or PAI-1-wt treatment for spontaneous apoptosis (*P < 0.001, n = 7) and for CPTinduced apoptosis (**P < 0.002, n = 7) respectively It has been found that PAI-1 plays an important role in migration and metastasis of tumour cells. PAI-1 may promote tumour cells invasion by regulating uPAR-dependent cell adhesion (Deng et al, 1996;Waltz et al, 1997). On the other hand, PAI-1 may inhibit integrin-and vitronectin-mediated cell migration by blocking α v β 3 binding to vitronectin (Stefansson and Lawrence, 1996;.…”
Section: Figurementioning
confidence: 99%